MODERNISATION OF PADDY CULTIVATION: AN ANALYSIS OF MECHANISATION AMONG PADDY GROWERS IN PALAKKAD DISTRICT OF KERALA STATE - Dr. Promodh . S (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The concept of Modernisation cannot be measured in absolute terms. What is modern now may not be considered modern tomorrow. Concept of modernisation may be different for different countries. Modernisation in agriculture could be defined either as modern or traditional using certain specific indicators. Farm mechanisation is an important indicator of modernisation (Kannaiyan, 2001). For the past several years the demand for agricultural machinery has increased substantially. Coming years, the major thrust would be mechanisation of farms and efficient use of available resources. Mechanisation is used as a proxy in estimating the level of technology in the agricultural sector. Mechanisation is an essential input like any other input such as fertilisers, seeds, and crop protection chemicals. It is one of the vital tools as a farmer has available to increase production and profitability and also reduce the drudgery of the human-powered output. Modern technology use in cultivation influence wellbeing of the farm communities in the district.